Virtualizing virtual channels for increased network-on-chip robustness and upgradeability - Evripidou, Marios; Nicopoulos, Chrysostomos; Soteriou, Vassos (My University, 2012)
The Network-on-Chip (NoC) router buffers are instrumental in the overall operation of Chip Multi-Processors (CMP), because they facilitate the creation of Virtual Channels (VC). Both the NoC routing algorithm and the CMP's cache coherence protocol rely on the presence of VCs within the NoC for correct functionality. In this article, we introduce a novel concept that completely decouples the number of supported VCs from the number of VC buffers physically present in the design. Virtual Channel Renaming enables the virtualization of existing virtual channels, in order to support an arbitrarily large number of VCs. Hence, the CMP can (a) withstand the presence of faulty VCs, and (b) accommodate routing algorithms and/or coherence protocols with disparate VC requirements. The proposed VC Renamer architecture incurs minimal hardware overhead to existing NoC designs and is shown to exhibit excellent performance without affecting the router's critical path
Keywords: Computer architecture; Routers (Computer networks); Networks on a chip; Hardware